The Impact of Student Loan Debt on Civic Engagement: Evidence from the College and Beyond II Dataset - Osasohan Agbonlahor (Education Sciences, 2025)
This study examines the relationship between student loan debt and civic engagement among college graduates, with particular attention to differential effects by field of study. Drawing on data from the College and Beyond II dataset, this research analyzes how varying levels of debt burden impact political and community participation among 1673 graduates, including 1059 liberal arts majors and 614 graduates from professional, STEM, and other fields. Employing OLS regression models with multiple measures of debt burden and distinct dimensions of civic engagement, this study finds that both medium and high levels of student loan debt (USD 201–500 monthly and >USD 500 monthly) are associated with significantly higher political engagement—a pattern that aligns with relative deprivation theory’s proposition that financial strain may motivate political action aimed at systemic change. This relationship is particularly pronounced among liberal arts graduates, who demonstrate stronger positive associations between debt and civic participation than their peers from other fields. Debt-to-income ratio analysis reveals a potential “sweet spot” at 10–15% of income, where debt appears to optimize civic engagement without overwhelming resources. These findings suggest that liberal arts education may fundamentally alter how graduates respond to financial constraints, potentially by providing analytical frameworks for understanding debt as a systemic issue and civic skills that facilitate participation despite economic pressures. The results challenge assumptions about debt’s uniformly negative civic consequences and highlight the importance of educational context in mediating economic effects on democratic participation.